Determination of the Hydrodynamic Characteristics of a Typical Inland Saline-Alkali Wetland in Northeast China - Liu, Yan; Cui, Geng; Tong, Shouzheng; Wang, Shan; Lu, Xianguo (Frontiers in Ecology and Evolution, 2022)
Hydrological connectivity in wetland ecosystems comprises a combination of hydrodynamic, hydrochemical, and biological characteristics. Hydrodynamic characteristics are important for the transmission of energy, matter, and information between surface water bodies and are critical for maintaining the health of wetland ecosystems. The hydrodynamic characteristics of wetlands are the temporal and spatial changes in the water level, flow direction, quantity, recharge, and discharge conditions of surface water and groundwater. Identifying wetland hydrodynamic characteristics is of great significance in revealing the hydrological patterns and biogeochemical phenomena of wetland ecosystems. The Momoge National Nature Reserve (MNNR) is a wetland located in the semi-arid region of northeast China, where the hydrodynamic characteristics are still unclear. In this study, water level monitoring of surface water and groundwater in MNNR was carried out, and wetland recharge and discharge were calculated according to a water balance analysis. The submerged wetland area was simulated based on an improved distributed hydrological model, SWAT-DSF, and compared with remote sensing data. The results showed that the dynamic characteristics of wetland surface water and groundwater are mostly affected by topography and recharge water sources. The water resources in the reserve are in a positive state of equilibrium in the wet season (September), with an equilibrium difference of 276.41 × 104 m3/day. However, it displays a negative equilibrium state in dry (November) and other (June) seasons, with an equilibrium difference of −12.84 × 104 m3/day and −9.11 × 104 m3/d, respectively. The difference between the submerged areas of the MNNR wetland during the wet and dry seasons was 250 km2.